2022
DOI: 10.1155/2022/1394088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Signal Pathways and Hub Genes of Pulmonary Arterial Hypertension by Bioinformatic Analysis

Abstract: Pulmonary arterial hypertension (PAH) is a progressive and complex pulmonary vascular disease with poor prognosis. The aim of this study was to provide a new understanding of the pathogenesis of disease and potential treatment targets for patients with PAH based on multiple-microarray analysis.Two microarray datasets (GSE53408 and GSE113439) downloaded from the Gene Expression Omnibus (GEO) database were analysed. All the raw data were processed by R, and differentially expressed genes (DEGs) were screened out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As shown in previous reports, the GO terms and KEGG pathways that hsa_circ_0007608 and hsa_circ_0064656 were enriched in were all related to the occurrence and regulation processes of PH. It is obvious that intracellular signal transduction is ubiquitous in the pathogenesis of PH in COPD [36] . Existing studies also show that ECM is implicated in the development of pulmonary vascular remodeling and high level of ECM-related proteins such as MMP-2 are associated with poor survival and prognosis of PH patients [37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous reports, the GO terms and KEGG pathways that hsa_circ_0007608 and hsa_circ_0064656 were enriched in were all related to the occurrence and regulation processes of PH. It is obvious that intracellular signal transduction is ubiquitous in the pathogenesis of PH in COPD [36] . Existing studies also show that ECM is implicated in the development of pulmonary vascular remodeling and high level of ECM-related proteins such as MMP-2 are associated with poor survival and prognosis of PH patients [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools has been widely applied in oncology to identify genetic changes and new potential biomarkers associated with various diseases [14][15][16] . Likewise, researchers have tried to apply bioinformtics analysis in the study of PH to to elucidate the potential functions of circRNAs related to PH, mostly based on databases and animal experiments [17][18][19][20][21][22][23][24][25][26] . However, few studies have utilized clinical samples with definite diagnosis of PH, and researches for PH in COPD are even fewer.…”
Section: W I T H D R a W N S E E M A N U S C R I P T D O I F O R D E ...mentioning
confidence: 99%
“…More and more researchers have extended this method to the field of PAH and achieved some important results [ 11 , 12 ]. However, most of these studies are limited to the theoretical stage without experimental verification [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin W et al found that TXNRD1 as a novel biomarker and potential therapeutic target for IPAH through Robust Rank Aggregation (RRA) method and experiments [ 14 ]. However, some of the current studies have the shortcomings of only making theoretical predictions and not further verifying the reliability of their prediction results through experiments [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We removed probe IDs that lacked corresponding gene symbols, and for genes with multiple probes, the highest value was considered the gene expression value. The gene expression matrix obtained was subjected to additional quality control through cluster and principal component analysis (PCA) [14] .…”
Section: Data Handlingmentioning
confidence: 99%